Food Insecurity Increased During the COVID-19 Pandemic in a Pediatric Cystic Fibrosis Population but Was Not Associated With Weight or Pulmonary Function. (7th June 2021) - Youngs, Rebecca; Kennel, Julie; Kotha, Kavitha; Hatsu, Irene; Gemma, Susan
Abstract: Objectives: This study's purpose is to determine changes in household food security status and nutrition-related anthropometrics and pulmonary function of children with Cystic Fibrosis during the COVID-19 pandemic. Methods: This retrospective study includede caregivers of children ages 2–18 years old with Cystic Fibrosis who had Ohio residency, a Forced Expiratory Volume in 1 second (FEV1 ) above 30% and consumed at least half of nutrient needs by mouth. After contacting all eligible households by phone, 30 subjects (50% response) enrolled. The validated 18 item Food Security survey module along with several supplemental questions was used to assess household food security status before and after the onset of the COVID-19 pandemic. A medical chart review collected demographics as well as weight (kg) and FEV1 (%) for the visit closest to the start of the pandemic (Jan-Mar 2020) and the most current visit (July-Dec 2020). Change in weight was categorized as desirable/undesirable based on clinic standards for using the fiftieth percentile as desirable. A paired t-test was used to determine change in FEV1 since the pandemic. Changes in food security status in relation to change in weight and change in FEV1 were determined using Fisher's test and Welch's t-test, respectively. Results: Participants were caregivers of children who were 9.96 ± 5.02 years old, 56% female, and 83% Caucasian. Ten % of participants ( n = 3) reported household food insecurity before the pandemic, which increased to thirty % ( n = 9) after the pandemic. Fifty percent of participants ( n = 15) experienced an undesirable weight gain (2.71 kg ± 6.32 kg; mean ± std dev). There was no change in FEV1 during the pandemic (−0.6% ± 9.02; P = .74). Changes in weight and FEV1 were not related to change in household food security status ( P = 0.287 and P = .088 respectively). Conclusions: Food insecurity increased during the COVID-19 pandemic; however, it was not related to undesirable weight change or decrease in FEV1 . The second part of this study will use semi-structured interviews to elucidate how families with children with cystic fibrosis coped with food insecurity during the pandemic. Funding Sources: Pulmonary Division, Nationwide Children's Hospital, Columbus OH